2022
DOI: 10.1111/are.15977
|View full text |Cite
|
Sign up to set email alerts
|

β‐Carotene of Arthrospira platensis versus vitamin C and vitamin E as a feed supplement: Effects on growth, haemato‐biochemical, immune‐oxidative stress and related gene expression of Nile tilapia fingerlings

Abstract: Microalgae are one of the most important sources of natural bioactive compounds, especially those revealing antioxidant activity such as β-carotene. Thus, this study was to compare the effects of dietary Vitamin C (L-ascorbic acid) or Vitamin E (αtocopherol) with β-carotene extracted from Arthrospira platensis on Nile tilapia (Oreochromis niloticus) on growth, feed utilization, blood indices, antioxidant activity, non-specific immunological indices and related gene expression. Three hundred and sixty apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 132 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…The levels of α-tocopherol found in the non-extruded and extruded A. platensis in this study were lower than those documented in the literature [ 50 ]. While the diminished α-tocopherol content warrants attention, it is essential to consider the broader nutritional context, as evidenced by studies such as the one by Taalab et al [ 51 ], which indicated that carotenoids like β-carotene, derived from Spirulina, could have a more pronounced effect than vitamin E on growth performance and various haemato-biochemical and immune-oxidative stress markers in broilers. Thus, while Spirulina supplementation enhances meat pigmentation and offers potential health benefits through its carotenoid content, the balance of nutrients, particularly the interplay between carotenoids and vitamin E, remains a crucial factor for optimizing both the quality of broiler meat and its acceptance among diverse consumer bases.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of α-tocopherol found in the non-extruded and extruded A. platensis in this study were lower than those documented in the literature [ 50 ]. While the diminished α-tocopherol content warrants attention, it is essential to consider the broader nutritional context, as evidenced by studies such as the one by Taalab et al [ 51 ], which indicated that carotenoids like β-carotene, derived from Spirulina, could have a more pronounced effect than vitamin E on growth performance and various haemato-biochemical and immune-oxidative stress markers in broilers. Thus, while Spirulina supplementation enhances meat pigmentation and offers potential health benefits through its carotenoid content, the balance of nutrients, particularly the interplay between carotenoids and vitamin E, remains a crucial factor for optimizing both the quality of broiler meat and its acceptance among diverse consumer bases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, VC supplementation obviously decreased the TG level of serum, suggesting that dietary VC levels did affect the coho salmon health. Blood TC including HDL-C as well as LDL-C levels had been documented to decrease [58][59][60][61], increase [36,62,63], or be independent [23,30,64] with dietary VC supplementation in fishes. VC had synergistic effects on cholesterol synthesis and catabolism; this might be the reason that VC had variable influences on serum cholesterol contents [65].…”
Section: Discussionmentioning
confidence: 99%